The Difference of the Effect of Reciprocal and Teaching Style on the Learning Outcomes of Service Basic Techniques - Igoresky, Andre; Tangkudung, James; Rihatno, Taufik (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
This study aims to see the differences in the effect of reciprocal and inclusion teaching styles on learning outcomes of basic service techniques. The type of this research is a quasi-experimental. The sample in this study were students of the Department of Sports Education, Faculty of Sports Science, Padang State University (UNP) 2018, as many as 44 people. The data were collected by conducting a placement test. Data analysis and hypothesis testing used comparative analysis techniques using the mean difference test formula (t test) with a significant level a = 0.05. From the data analysis, it can be concluded that there is a difference in the effect of reciprocal and inclusion teaching style on the learning outcomes of student basic service techniques, with the result of the Ã¢â‚¬Å“tÃ¢â‚¬Â test coefficient, namely tcount (3.38) which is greater than ttable (1.680).